1986
DOI: 10.1007/bf01655238
|View full text |Cite
|
Sign up to set email alerts
|

Total thyroidectomy: Complications and technique

Abstract: During the 27-year period from 1957 to 1984, four hundred thirty patients underwent total thyroidectomies for malignant or benign disease of the thyroid gland at our institutions. Thyroid cancer was found in 83.4% of cases, and 47.2% of these had concomitant lymph node dissections. Transient recurrent laryngeal nerve injury occurred in 6.2% of the entire series. Permanent unilateral vocal cord paralysis occurred in 2.5% of the patients operated on, although only 1 patient (0.45 %) sustained this complication i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
114
2
16

Year Published

1992
1992
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(140 citation statements)
references
References 16 publications
8
114
2
16
Order By: Relevance
“…Another complication that has enjoyed some attention is hypoparathyroidism which, in our series, was present in 9.5% of the cases, matching the literature information, which varies from 0 to 16.8% 3,4,6,7,9,12 . In one case, this complication was temporary, it reverted 35 days later with specific treatment, and such fact was shown by other authors 4,6,9 .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Another complication that has enjoyed some attention is hypoparathyroidism which, in our series, was present in 9.5% of the cases, matching the literature information, which varies from 0 to 16.8% 3,4,6,7,9,12 . In one case, this complication was temporary, it reverted 35 days later with specific treatment, and such fact was shown by other authors 4,6,9 .…”
Section: Discussionsupporting
confidence: 88%
“…In one case, this complication was temporary, it reverted 35 days later with specific treatment, and such fact was shown by other authors 4,6,9 . De Jong et al showed that hypoparathyroidism was present in 3% of the patients who were submitted to total completion thyroidectomy and used vitamin D and calcium for some months with clinical signs and symptoms reversion.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Several thyroid conditions such as Graves' disease, recurrent thyroid disease, and thyroid carcinoma carry a higher risk of postoperatively developing transient and permanent hypocalcemia [4]. The reported complication rate for permanent hypocalcemia varies signifi cantly, ranging from 0.5 to 11.0% [5]. Different types of surgeries and benign and malignant thyroid diseases in the same series make the description of related risk factors diffi cult.…”
Section: Discussionmentioning
confidence: 99%